Pelatihan Pembuatan Dendeng bagi Kelompok Pemburu dan Penjual Daging Rusa di Kampung Ukopti, Kawasan Penyangga Cagar Alam Pegunungan Arfak Papua Barat - Manik, Hotlan; Randa, Sangle Yohannes; Palulungan, John Arnold (IGKOJEI: Jurnal Pengabdian Masyarakat, 2020)
ABSTRACT The Arfak Mountains Natural Reserve (CAPA), which is located in the Bird's Head Peninsula region of West Papua, Indonesia, covered an area of about 45,000 km2. The area is located within the three different administrative areas, including Manokwari, Manokwari Selatan, and Pegunungan Arfak Regencies. Ukopti Village is located in the District Tanah Rubuh Manokwari District which is a buffer zone directly adjacent to The Nature Reserve Area Mountains Arfak (CAPA). The economic circumstances village community is marginal and underprivileged, with their main livelihood obtained from their mostly small farms. The farms' result is often uncertain so they depend on other alternatives such as wildlife, especially deer hunting. Based on the decision of the Minister of Forestry and Plantation No: 682/Kps-II/1988 on the establishment of the Timor deer (Cervus timorensis) for game hunting in Papua, the deer has the potential to improve the community's nutrition and economy when compared to a better-off society, which usually has access to conventional livestock. Most of the community groups normally sell their catch in the form of fresh deer meat and bacon, so oftentimes the quality of the products are lower because they are not sold quickly enough and the distance to the district town is quite far, the expensive cost of transport only exacerbates the problem. The training lasted for eight months and was held at Kampung Ukopti Land District Rubuh Manokwari District. Two groups acted as partners or the target groups of this activity, they are the hunters and deer-butchers groups. The activities of this training include lectures, demonstrations, and hands-on participation. Results of the practice of making deer-jerky had been adopted by the community/partners who have received the training, as shown by the products produced according to the example given to the participants. This activity is highly appreciated by the people of Kampung Ukopti, indicated by the presence of local officers and most of the people during the activity. Keywords: : Reindeer jerky; Entrepreneur; The Arfak Mountains Natural Reserve Area (CAPA ABSTRAK Cagar Alam Pegunungan Arfak (CAPA) yang terletak di wilayah Kepala Burung Papua Barat, Indonesia, luasnya sekitar 45.000 km2. Wilayah tersebut terletak di tiga wilayah administratif yang berbeda yaitu Kabupaten Manokwari, Manokwari Selatan dan Pegunungan Arfak. Kampung Ukopti terletak di Distrik Tanah Rubuh Kabupaten Manokwari yang merupakan daerah penyangga (buffer zone) yang berbatasan langsung dengan kawasan Cagar Alam Pegunungan Arfak (CAPA). Keadaan ekonomi masyarakat desa yang marjinal dan kurang mampu yang diperoleh dari kebun yang tidak menentu sehingga alternatif lainnya bergantung pada satwa liar, khususnya berburu rusa. Berdasarkan Keputusan Menteri Kehutanan dan Perkebunan Nomor: 682 / Kps-II / 1988 tentang Penetapan Rusa timor (Cervus timorensis) untuk pemburuan di Papua, Rusa timor merupakan salah satu spesies yang berpotensi untuk meningkatkan gizi dan gizi. Masyarakat ekonomi jauh akan mengakses ternak konvensional. Kelompok masyarakat yang selama ini hanya menjual hasil tangkapannya berupa daging rusa segar dan bacon seringkali kualitas mangsanya mudah rusak karena tidak laku dan jarak ke kota kabupaten cukup jauh serta sisi angkutan yang cukup mahal. Kegiatan ini berlangsung selama delapan bulan bertempat di Kampung Ukopti Tanah Distrik Rubuh Kabupaten Manokwari. Dua kelompok yang dijadikan mitra atau kelompok sasaran kegiatan tersebut adalah kelompok berburu dan menyembelih rusa. Tahapan dari kegiatan ini meliputi ceramah, demonstrasi dan peserta langsung mempraktekan pembuatan dendeng. Hasil praktek pembuatan dendeng harus diadopsi oleh masyarakat / mitra yang sudah mendapatkan pelatihan, terlihat dari produk yang dihasilkan sesuai contoh yang diberikan peserta. Kegiatan ini mendapat apresiasi yang tinggi dari masyarakat Kampung Ukopti yang ditunjukkan dengan kehadiran petugas dan sebagian besar masyarakat selama kegiatan berlangsung. Kata kunci: Dendeng rusa; Pengusaha; Kawasan Cagar Alam Pegunungan Arfak (CAPA)